Absorption and Fluorescence Mechanisms of Red Mega 480 Laser Dye Coupled with Silver Nanoparticles - Dadami, Sunanda; Tangod, Vadiraj (The Nucleus, 2023)
Herein, we used the chemical reduction method to synthesize silver nanoparticles. The characterization of synthesized particles is done using UV-Vis, SEM, and TEM techniques, which reveal sizes in the range of 4–12 nm. In this particular instance, the optical absorption spectra of synthesized silver nanoparticles produced a maximal spike in the 400–410 nm region. This spike is attributed to surface plasmon resonance. The spectra of emission and absorption intensities of the exceptionally brilliant laser Red Mega 480 dye in alcohol solvents with the addition of silver nanoparticles indicate quenching. This is related to the size, shape, and transfer of energy between silver nanoparticles and dye. The quenching of fluorescence intensity in the presence of nanoparticles with Red Mega 480 dye leads to advancements in biomolecular labeling, printing technology, 3D graphics, glossy painting, fluorescence patterning, and cancer treatment. The optical properties of isolated colloidal particles, and in particular their dependence on particle size effects, have been intensively investigated through Mie’s scattering theory. In the present case, the absorption spectra of silver nanoparticles of size 4–12 nm have a maximum peak in the range 400–410 nm, respectively, related to the plasmon resonance formed due to the nanosized silver nanoparticles. This absorption band (surface plasmon resonance, SPR) results from interactions of free electrons confined to small metallic spherical objects with incident electromagnetic radiation. The observed plasmon resonance band shows the silver nanoparticles are spherical in shape. Optical absorption and fluorescence of the highly fluorescent laser dye Red Mega 480 in alcohol solvents with the attachment of silver nanoparticles show quenching in absorption and fluorescence intensities. This is due to size, shape, coupling between silver nanoparticles and dye, and energy transfer between silver and dye. Quenching of fluorescence in the presence of nanoparticles for Red Mega 480 leads to many applications, especially advancements in biomolecular labeling, fluorescence patterning, and chemotherapy in cancer treatment.